2019
DOI: 10.3889/oamjms.2019.682
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure Variation-Guided Fluid Therapy during Supratentorial Brain Tumour Excision: A Randomized Controlled Trial

Abstract: BACKGROUND: Goal-directed fluid therapy (GDFT) improved patient outcomes in various surgical procedures; however, its role during mass brain resection was not well investigated. AIM: In this study, we evaluated a simple protocol based on intermittent evaluation of pulse pressure variation for guiding fluid therapy during brain tumour resection. METHODS: Sixty-one adult patients scheduled for supratentorial brain mass excision were randomized into either GDFT group (received intraoperative fluids gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…Between the CVP group, which maintained a CVP of 5-10 cm-H2O, and the PPV group, which maintained a PPV below 13%, in patients undergoing a brain tumor surgery, the latter had better postoperative hemodynamic stability and less postoperative fluid requirement [69]. The PPV-guided GDFT during supratentorial tumor resection had a comparable brain relaxation scale, low serum lactate levels, more intra-operative fluids, and higher urine output than the standard care group [70]. In the sitting position for neurosurgery, measuring the PPV and PVI with an ear sensor predicted fluid responsiveness well, but the PVI could not be predicted with a finger sensor.…”
Section: Gdft During Neurosurgerymentioning
confidence: 93%
See 1 more Smart Citation
“…Between the CVP group, which maintained a CVP of 5-10 cm-H2O, and the PPV group, which maintained a PPV below 13%, in patients undergoing a brain tumor surgery, the latter had better postoperative hemodynamic stability and less postoperative fluid requirement [69]. The PPV-guided GDFT during supratentorial tumor resection had a comparable brain relaxation scale, low serum lactate levels, more intra-operative fluids, and higher urine output than the standard care group [70]. In the sitting position for neurosurgery, measuring the PPV and PVI with an ear sensor predicted fluid responsiveness well, but the PVI could not be predicted with a finger sensor.…”
Section: Gdft During Neurosurgerymentioning
confidence: 93%
“…The PPV and PVI have also been reported to be good predictors of fluid reactivity during brain surgery [69][70][71][72]. Between the CVP group, which maintained a CVP of 5-10 cm-H2O, and the PPV group, which maintained a PPV below 13%, in patients undergoing a brain tumor surgery, the latter had better postoperative hemodynamic stability and less postoperative fluid requirement [69].…”
Section: Gdft During Neurosurgerymentioning
confidence: 98%
“…When MAP remained < 60 mmHg despite the fluid intervention or MAP was < 60 mmHg with PPV ≤ 14% and SV increased less than 10%, vasopressor therapy was initiated, in the form of an ephedrine bolus of 6 mg with a maximal cumulative dose of 30 mg. If needed, a continuous infusion of norepinephrine (0.05 μg·kg -1 ·min -1 ) was administered (Hasanin et al 2019 ).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, very few studies have suggested the efficacy of PPV in the neurosurgical population. [11][12][13][14] Hence, this study aimed to compare the effect of PPVguided fluid management with the conventional CVP-guided method in patients undergoing supratentorial tumor surgeries. The primary outcome was to compare the intraoperative fluid requirement between CVP-and PPV-guided management.…”
Section: Introductionmentioning
confidence: 99%